The War on Normal People: The Truth About America's Disappearing Jobs and Why Universal Basic Income Is Our Future (AmeriQuests, 2022)
Andrew Yang's 2018 book The War on Normal People, seems to ignore traditional categorizations of moderation and progressivism by focusing on a different divide: the gap between “normal people” and those who live “inside the bubble.”